«Studia Humanitatis» Today: Grassi’s Renewal - Sánchez Espillaque, Jéssica (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2021)
Faced with the current need for a renewal of education, the rehabilitation of Renaissance humanism is proposed as a way of attempting to respond to the present crisis in the humanities. Such a task takes up the interpretation of humanism made by the philosopher Ernesto Grassi; from whose thought will derive, on the one hand, the demand to carry out a revision of what humanism is, and, on the other hand, the revaluation of the humanist tradition as eminently philosophical thought.